Monkeypox — Enhancing public health preparedness for an emerging lethal human zoonotic epidemic threat in the wake of the smallpox post-eradication era. (January 2019) - Petersen, Eskild; Abubakar, Ibrahim; Ihekweazu, Chikwe; Heymann, David; Ntoumi, Francine; Blumberg, Lucille; Asogun, Danny; Mukonka, Victor; Lule, Swaib Abubaker; Bates, Matthew; Honeyborne, Isobella; Mfinanga, Sayoki; et al.
Highlights: Three patients were diagnosed with monkeypox in the United Kingdom in September 2018 the index case being from Nigeria. Nigeria is currently experiencing a large outbreak of monkeypox with a total of 116 cases as per September 2018. The median age of the cases are 31 years. The cases belong to an age group not immunized against smallpox. After the eradication of smallpox and the end of the immunization program a nice for a new poxvirus may have been created. Abstract: The identification of monkeypox in 3 separate patients in the United Kingdom in September raised media and political attention on an emerging public health threat. Nigeria, whose last confirmed case of monkeypox was in 1978, is currently experiencing an unusually large and outbreak of human monkeypox cases, a 'One Human-Environmental-Animal Health' approach is being effectively used to define and tackle the outbreak. As of 13th October 2018, there have been one hundred and sixteen confirmed cases the majority of whom are under 40 years. Over the past 20 years ten Central and West African countries have reported monkeypox cases which have risen exponentially. We review the history and evolution of monkeypox outbreaks in Africa and USA, the changing clinical presentations, and discuss possible factors underlying the increasing numbers being detected including the cessation of smallpox vaccination programs. Major knowledge gaps remain on the epidemiology, host reservoir, and emergence, transmission, pathogenesis and prevention of monkeypoz.